(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Information age has brought about a revolution in technological advancement. The industrial revolution propelled the world into a new era of greater mechanical advantage and shaped our current world. India was suffering with division and lack of political stability at that time and was not able to capitalize on its resources, then. So, when the world ushered into a new era of digitization, Digital India was launched to digitize the entire ecosystem and to make full use of our natural and human resources. Digital India aimed to capitalize on this opportunity by positioning ourselves in the best way possible. Although these programs have come a long way forward, they have faced major challenges. The successful launch and growth of E-governance platforms and other technological advancements are leaving many Indians behind and this divide is to be checked by increasing the digital literacy of the average Indian. Are the various programmes under this digital India scheme dealing with most of these problems and are they setting the stage for a bright and technically advanced future is to be seen.